(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the pivotal role of instructors in the purposeful development of cognitive processes among higher education students within contemporary educational paradigms. In an environment where the emphasis shifts from passive knowledge transfer to actively fostering metacognitive skills, critical thinking, and digital literacy, the educator’s role becomes central to stimulating cognitive functions such as perception, attention, memory, thinking, imagination, and speech. The article examines current theoretical foundations and innovative practical mechanisms through which instructors can effectively influence these processes, including the application of active and interactive methodologies, proble-based and project-based learning technologies, and the creation of a cognitively stimulating digital and physical learning environment. Advanced strategies for instructor influence on students’ cognitive development are discussed, emphasizing their significance for academic success, the formation of professional competencies, and adaptation to the challenges of the 21st century.